2013
DOI: 10.1111/ppa.12037
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility evaluation of Picea abies and Cupressus lusitanica to the pine wood nematode (Bursaphelenchus xylophilus)

Abstract: Pine wilt disease (PWD), recently introduced into Europe, is caused by the pine wood nematode (PWN) Bursaphelenchus xylophilus and is a devastating illness that affects mainly pine trees. It is known that the PWN is capable of infecting other conifers; however, there is currently no information on which other plant species may be susceptible to PWD. In this study, the potential susceptibility of two common species of European forests, Picea abies and Cupressus lusitanica, to PWN was assessed through the monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 30 publications
4
24
1
Order By: Relevance
“…We found a positive relationship between nematode migration and polyphenol concentration of branch segments, contradicting previous research reporting that PWN resistant species or varieties accumulate more phenolic compounds than susceptible ones in response to PWN infection (Kuroda et al 2011;Nunes da Silva et al 2013). Some particular phenolic compounds found in resistant pine species, i.e., stilbenoids, have been reported to show nematicidal activity to the PWN in in vitro assays (Suga et al 1993), although their role as a factor of resistance in vivo has been questioned (Zhang et al 2013).…”
Section: Treescontrasting
confidence: 93%
See 1 more Smart Citation
“…We found a positive relationship between nematode migration and polyphenol concentration of branch segments, contradicting previous research reporting that PWN resistant species or varieties accumulate more phenolic compounds than susceptible ones in response to PWN infection (Kuroda et al 2011;Nunes da Silva et al 2013). Some particular phenolic compounds found in resistant pine species, i.e., stilbenoids, have been reported to show nematicidal activity to the PWN in in vitro assays (Suga et al 1993), although their role as a factor of resistance in vivo has been questioned (Zhang et al 2013).…”
Section: Treescontrasting
confidence: 93%
“…Moreover, nematode migration has been related to the virulence of the PWN (Kuroda 2008b;Son et al 2010). In particular, nematode migration has been found to be slower or even completely blocked in resistant conifer species (Oku et al 1989;Nunes da Silva et al 2013), and in resistant genetic variants (Kuroda 2004;Kuroda et al 1991). Some examples that contradicted this were also reported, however, indicating that migration and colonization ability do not completely determine the susceptibility of pines to the PWN (Mori et al 2008;Eo et al 2011).…”
mentioning
confidence: 99%
“…The loss of photosynthetic pigments can occur from an early stage of the PWD and can be used to assess the degree of tissue damage caused by B. xylophilus (Nunes da Silva et al. ). In the current work, in the absence of chitosan, 24 dai both P. pinaster and P. pinea PWN‐inoculated plants experienced a decrease in total chlorophylls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1000 PWNs using the technique described by Nunes da Silva et al. (). In addition, 80 plants of each species (20 for each chitosan solution and 20 controls) were inoculated with deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…Both molecules are known to induce the biosynthesis of several antimicrobial compounds, namely phytoalexins (Vasyukova et al, 2001), callose (Ren et al, 2001) and lignin (Barber et al, 1989). Several papers have reported that chitosans and CHOs can be used, for example, to enhance the plant's defense against bacteria (Tikhonov et al, 2006; Rabea and Steurbaut, 2010), fungi (Park et al, 2002; Trotel-Aziz et al, 2006) and nematodes (Khalil and Badawy, 2012; Nunes da Silva et al, 2014). Besides plant defense, a broader range of influences in plant growth and development have been shown.…”
Section: Introductionmentioning
confidence: 99%